Analysis of Learning Systems in Indonesia and Japan - Miftachul Amri; Melly Susanti; Satoshi Kusaka; Loso Judijanto; Fien Pongpalilu; Reza Yuridian Purwoko (Journal of Innovation in Educational and Cultural Research, 2024)
This study compares the education systems in Indonesia and Japan, focusing on teacher quality enhancement. Teacher quality significantly influences educational outcomes, necessitating targeted efforts to improve their competence and performance. The government has implemented several initiatives in Indonesia, including teacher certification programs and professional development efforts. However, challenges such as unequal distribution of teacher quality and limited access to advanced training persist. Meanwhile, Japan exemplifies a robust teacher preparation and monitoring system with rigorous recruitment processes, periodic evaluations, and structured professional development. This research utilized a qualitative descriptive method and a Systematic Literature Review (SLR), supplemented by surveys and interviews conducted with educators and students involved in a cultural exchange program. The findings highlight key differences in teacher training and evaluation frameworks between the two countries, with Japan's structured approach serving as a model for Indonesia. The study concludes that adopting comprehensive strategies, such as enhanced teacher preparation, continuous evaluation, and professional development, can elevate teacher quality in Indonesia. The research contributes to the discourse on education reform by emphasizing the critical role of teacher quality in shaping national educational success and recommending actionable strategies for policymakers.